(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Large cities centered on the large river are often found that many of the slums are constructed close to the shore, owing to low land costs and the flooding of river waters during the rainy season. Due to the financial and physical features of the urban slums, the public waste management scheme is seldom encouraged. The waste collection method also struggles because of the tightly constructed houses and narrow roads and because of analphabetism that does not dump waste at the municipality’s waste bin or designated location. The volume of solid waste disposed of at the precise point chosen by the town, as well as the waste deposited on the ground or side of the ground, of which the Environmentalist is obliged, and how this waste pollutes water. The volume of solid waste not adequately dumped is determined by comparing the overall solid household waste and the sum of waste received by the municipality. The water quality measurement metric involves pH, turbidity, BOD, COD, electrical conductivity, TDS and TS. They demonstrate why and how to enhance the water quality of the river and the ecosystem of the municipality.